Montgomery marketing and management corp. - Fernandez, Mary Genevere F. (University of the Philippines Diliman, 2004)
The rapid pace of technological, social, economic and regional developments provides new opportunities for companies to outperform their competitors in a free market environment. As industries continue to evolve and business processes become more and more technology-driven, companies are compelled to integrate a technological dimension in their corporate strategies if they are to take advantage of these opportunities. As such, the formulation of a technology strategy becomes not only an essential but also a critical task in managing and sustaining the organization in the face of the competition. But before an effective technology strategy is established, companies need to assess their own technological capabilities and practices in the management of technology especially if their chosen technologies are already being used and has been in existence for quite some time in the market. One of the most effective ways to do this is by performing a Technology Audit. As defined by Khalil, a Technology audit is an analysis performed to identify the strengths and weaknesses of the technological assets of the organization. This paper is the official report on the Technology Audit performed for Montgomery Marketing and Management Corporation, a company engaged in the development of applications for Smart Card technology, a technology considered as already in its mature stage in the Technology Life Cycle. The audit was done in partial fulfillment of the requirements in the course Technology Management 299.2. The audit was chosen to be the focus of the course project to serve as an initial step in properly developing the technology strategy of Montgomery, to which this author is currently connected. The first section discusses the Scope and Objectives of the project, detailing the framework that was used, the methodology and the expected benefits and project outputs. The background of the project follows, where the technology and industry are reviewed, citing the advantages and applications of smart cards in different parts of the world. A primer on Loyalty Programs is also included in order to orient the reader on the company's main business. The last part of the section describes the company's background and its general business processes. The third section, which is the body of this paper discusses the audit findings according to the Technology Audit Model (TAM) framework which was utilized for this project. The findings indicate that the company has an overall assessment of below average in the categories and assessment areas of the TAM especially in the area of back office operations or process technologies. Action plans and recommendations for applying then discussed in the fourth and last section with emphasis on the recommendation for applying the Microsoft Solutions Framework (MSF) model to Montgomery's application development. References are indicated in the fifth section and the last section contains the appendices. The TAM Checklist is marked as Appendix A while the white paper for the MSF Process Model is marked as Appendix B.